슬러리내 석탄입자의 광산란 특성 평가 - 황문경(Mun Kyeong Hwang); 남현수(Hyun Soo Nam); 김규보(Kyu Bo Kim); 송주헌(Ju Hun Song) (한국수소 및 신에너지학회 논문집, 2013)
In a direct coal fuel cell (DCFC) system, it is essential to identify volume fraction of coal suspended in electrolyte melt in order to control its dispersion and fluidity. This requirement is compelling especially at anode channel where hot slurry is likely to flow at low velocity. In this study, light scattering techniques were employed to measure the volume fraction for a pulverized coal suspension with relatively high absorption coefficient. The particle size, scattering angle, and volume fraction were varied to evaluate their effects on the scattering behavior as well as scattering regime. The larger coal size and smaller forward scattering angle could provide a shift to more favorable scattering regime, i.e., independent scattering, where interferences of light scattering from one particle with others are suppressed.